Exploring the Impact of Novel Prebiotic Substrates on Lactobacillus casei and Lactobacillus acidophilus under bile stress exposure - Sandoval C., Vidal A. (Zamorano: Escuela Agrícola Panamericana, 2024)
The increase of interest in probiotics to promote better health shows a substantial promise to expand the food industry into new fields. The gut microbiota has several beneficial effects on human health and the search for enhancing it to maintain and foster a larger amount of these probiotics has led to the emergence of probiotics, prebiotics, and symbiotics products. It has been identified that Carao (Cassia grandis), Teosinte (Dioon mejiae), South American palm weevil (Rhynchophorus palmarum), and Caesar’s mushroom (Amanita cesarea) have bioactive compounds with prebiotic characteristics and significant nutritional applications. The study aims to carry out a literary review of probiotics and prebiotics and their relationship with the human microbiome, and also to investigate the behavior of L. casei and L. acidophilus under bile (Oxgall 0.3%) stress in the presence of Carao, Teosinte, ceasar mushroom and South American palm weevil. The software Statistical Analysis Systems (SAS) was used and examined using the General Linear Model (PROC GLM) for the main effects (treatments and time). Duncan test was used to determine the statistical differences (p < 0.05) among the main effects. In the case of the literary review, 64 documents were reviewed, of which 11 did not meet the established criteria. The selected ones cover the microbiome, probiotics, their relationship in the digestive tract and bile tolerance evaluation. The analyzes showed that for both bacteria L. acidophilus and L. casei, treatments with prebiotic potential did not reduce biliary stress; in addition, the biliary stress generated (0.3%) despite being a similar concentration of small intestine this concentration acts as sublethal stress to L. casei and L. acidophilus.